Makam Sunan Bonang Tuban Jawa Timur: Pengawasan Panoptik sebagai Upaya Perlindungan Cagar Budaya - Ghozi, Ahmad; Fauziyah, Nailul; Amin, Saiful (JOM, 2024)
The application of panoptic surveillance in Sunan Bonang Tomb, Tuban, East Java is expected to create a safe and secure environment, so that the cultural and historical values contained therein can continue to be passed on to future generations. This study aims to examine the effectiveness of panoptic surveillance in preserving cultural heritage, as well as the long-term impact of the application of panoptic surveillance in efforts to preserve cultural heritage sites in the tomb of Sunan Bonang Tuban. This research is descriptive in nature with a qualitative approach conducted in an explanatory manner to explore the effectiveness of panoptic surveillance in preserving cultural heritage at the tomb of Sunan Bonang Tuban. In this study, researchers investigated a cultural group in a natural environment over a sufficient period of time, with an approach that was flexible and developed according to field conditions. As one of the efforts in maintaining and preserving the cultural heritage in Sunan Bonang Tomb in Tuban, panoptic surveillance, which refers to a broad and comprehensive surveillance system, was applied as a strategy to protect Sunan Bonang Tomb in Tuban, East Java. Several panoptic signs found in Sunan Bonang Tuban Tomb, ranging from the Jaba, Jaba Tengah, to Jeroan, are a conscious effort to maintain and provide important education to all parties.